Prevalence of Rhinitis in Athletes: Systematic Review. (9th August 2017) - Surda, Pavol; Walker, Abigail; Putala, Matus; Siarnik, Pavel
Abstract : Background . Prevalence of rhinitis in athletes has frequently been studied and varies widely from 27% to 74%. The aim of this systematic review was to examine the prevalence of rhinitis in athletes, to specifically compare the evidence of rhinitis in land-based and aquatic athletes. Methods . Systematic search of MEDLINE, EMBASE, and the non-MEDLINE subset of PubMed was performed from inception to March 8, 2016, to identify studies on rhinitis in athletes. Results . Of the 373 identified unique articles, a total of 13 studies satisfied the criteria for this review. The final group contained 9 cohort and 4 case-control studies. We found 10 studies that reported the prevalence of allergic rhinitis (21%–56.5%). In contrast, nonallergic rhinitis was identified by only 1 author (6%). We have also evaluated the prevalence of rhinitis in the separate subgroups (land, water, and cold air) where swimmers seem to be the most affected (40%–74%), followed by cross-country skiers (46%) and track and field athletes (21 to 49%). Conclusion . We did not reveal any convincing trend of a higher prevalence in land-based athletes compared to general population. By contrast, aquatic and cold air athletes demonstrate increased prevalence reflecting the irritant effects of their environment on the nasal mucosa.